Professional Learning in Education - Aelterman, Antonia; Vanderlinde, Ruben; Tuytens, Melissa; De Wever, Bram (Academia Press, 2016)
Educational quality is at the center of debates worldwide. In all these debates, teachers are considered as the critical actors determining to a large extent the quality of our educational systems. At the same time, doubts are expressed related to teachers' quality as well as to the education or training of teachers. In this context, policy debates underline the need for 'excellent' teachers and 'excellent' teacher education. 'Excellence' became the mantra in all educational policy debates. This book presents a model for teachers' professional development together with the three central themes: (1) professionalism of teacher educators, (2) professional development of (student) teachers, and (3) (student) teacher practices. The different chapters in this book discuss these themes in detail and originated from an open call launched at the ISATT 2013 conference that was organized around the central theme of 'Excellence of teachers?'. Urgent issues that address practitioners, teacher educators, and researchers are discussed throughout the chapters and general research challenges for teacher education researchers are put forward in the epilogue of this book.